2008
DOI: 10.1177/07316844070799152008
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Finite Element Analysis of Modified ASTM D3039 Tension Test for Marine Grade Polymer Matrix Composites

Abstract: The variability of tensile mechanical properties of a polymer matrix composite material with woven fabric reinforcement is studied using both experimental work and numerical simulations. Four E-glass/vinyl ester composite plates were fabricated using the vacuum-assisted resin transfer molding (VARTM) by a US Navy contractor. The materials and process selected are representative of Marine grade composites typically used by the US Navy. Standard and modified D3039 tensile coupons were obtained from the plates an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Composites are inherently complex, involving several materials with highly different mechanical properties, anisotropies and dynamic behaviours and a large number of methods for combining the materials. When material data are measured, 31–34 it is obvious that the results depend on many parameters, such as type of fibre, reinforcement, fibre layup, resin, production method and test method, and also on the type of core in the case of sandwich structures. In Håkansson 35 and Bull, 36 it was shown that the brand of fibre and manufacturer of the reinforcement can have a large impact on the mechanical properties of the laminate, even though the materials are allegedly the same.…”
Section: Description Of Structures and Materialsmentioning
confidence: 99%
“…Composites are inherently complex, involving several materials with highly different mechanical properties, anisotropies and dynamic behaviours and a large number of methods for combining the materials. When material data are measured, 31–34 it is obvious that the results depend on many parameters, such as type of fibre, reinforcement, fibre layup, resin, production method and test method, and also on the type of core in the case of sandwich structures. In Håkansson 35 and Bull, 36 it was shown that the brand of fibre and manufacturer of the reinforcement can have a large impact on the mechanical properties of the laminate, even though the materials are allegedly the same.…”
Section: Description Of Structures and Materialsmentioning
confidence: 99%
“…In the following discussion we seek to properly predict the strength properties of the bending coupons using the probabilistic FEA model. As recommended in previous work 10,12 the COV of material properties will be scaled by a factor of 1.5 and a correlation length over element width of 20 will be used for best correlation between the probabilistic model results and experimental results.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…The Monte Carlo numerical simulation is a powerful tool for analyzing complex structures with real-life property uncertainty. [10][11][12][13][14] This method predicts the response of a structure subjected to variable design parameters of known or pre-described probability distributions. Using statistical sampling techniques a set of values of the basic random variables are generated according to their corresponding probability distributions.…”
Section: Probabilistic Fea Model Using Monte Carlo Simulationsmentioning
confidence: 99%
“…Jeong and Shenoi 5,6 estimated the probabilistic strength distribution of composite laminates with a variety of stacking sequences subjected to an out-of-plane load. Nader et al 7 performed a probabilistic failure analysis of a cross-ply laminate subjected to tension. In all of these investigations the ultimate limit state (ULS) was considered to be the first ply failure.…”
Section: Probabilistic Analysesmentioning
confidence: 99%